A method for filamentous fungal growth and sample preparation aimed at more consistent MALDI-TOF MS spectra despite variations in growth rates and/or incubation times. Issue 1 (3rd May 2019) - Reeve, Michael A; Bachmann, Denise
Abstract: Matrix-assisted laser-desorption and ionization time-of-flight mass spectrometry can be used for the characterization and identification of filamentous fungi, for which it is desirable to have a means of growth in which the resulting spectra remain as consistent as possible over time. To this end, we initially opted for growth in oil-overlaid small-volume liquid culture, using a medium (Czapek Dox) not containing significant amount of proteins or peptides, and with protein extraction from the entire culture volume. For both 3-week and 10-day time courses, however, we observed marked spectral changes over growth time, along with lower peak richness compared to agar-plate controls. Guided by the above, we next employed a more nutrient-rich MALDI-TOF MS-compatible liquid-culture medium, now used without an oil overlay. For a 10-day time course, we again observed marked spectral changes over growth time, along with lower peak richness compared to agar-plate controls. Finally, we opted for a method employing filter-paper-supported growth in the same MALDI-TOF MS-compatible rich medium within sealed 1.5 ml Eppendorf tubes, again with protein extraction from the entire culture volume. Using this final method, while we observed significant spectral changes between 2 days and 3 days, from 3 days to 10 days the spectra remained very consistent, with comparable peak richness to agar-plate controls. This method gave slightly better identifications and lower spectral variance compared to agar-plate controls, and the use of this method for the construction of growth-time-point-specific databases for fungal identification is discussed.